CLEANER PRODUCTION POTENTIAL EVALUATION. CASE STUDY MINE OF CARBONATED SILTS IN CAYO MOA BAY, CUBA - Cervantes Guerra, Yosbanis; Pierra Conde, Allan; Vandecasteele, Carlo (Revista de Innovación Social y Desarrollo, 2019)
The purpose of this study was to do a Rapid Plant Assessment (RPA) in order to identify Cleaner Production options in extracting carbonated silts at Cayo Moa bay. To fulfill this purpose, the executing mining processes were identified and characterized, and the Cleaner Production potentials were defined in semi-quantitatively way. The extraction process is not optimal; because the excavator used does not have the necessary automation for using the deposit rationally. This causes irregularities in the mining front influencing the dynamics of the sediments, energy distribution means and negatively impacts on fauna and vegetation areas surrounding the dredging